Analisis Faktor-faktor yang Mempengaruhi Pengangguran Terdidik Tingkat Universitas di Provinsi Pulau Jawa Tahun 2017–2024: Pendekatan Regresi Data Panel - Adela Yunensy; Nurjannah Rahayu Kistanti (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
Educated unemployment is a challenge for economic development, especially in Java, the center of higher education and national economic activity. This study aims to analyze the influence of the Human Development Index (HDI), Gross Regional Domestic Product (GRDP), Labor Force Participation Rate (LFPR), and Regional Minimum Wage (RMW) on the unemployment rate of university graduates in six provinces in Java for the period 2017–2024. This study uses panel data regression with the Random Effect Model (REM) approach. The results show that the HDI and GRDP have a positive and significant influence on educated unemployment in Java. The LFPR variable has a negative and significant influence on educated unemployment in Java. Meanwhile, the RMW variable has no effect on educated unemployment in Java. Suggestions from this study are that the government must ensure that the increase in HDI is balanced with equivalent employment opportunities, synergy between the world of education and the business world needs to be strengthened, there is a policy of active involvement of new graduates in productive activities, and increase productivity and the provision of work space.